2015
DOI: 10.5812/ircmj.28363
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Neuroanatomy of the Human Mirror Neuron System: Impact on Functional Recovery of Ischemic Hemiparetic Patients

Abstract: Background:Considering the higher activity of mirror neuron system in females, they frequently have better performance in empathy, interpersonal sensitivity, and emotional recognition compared to males.Objectives:The purpose of this study was to assess whether gender difference in neuroanatomy of the human mirror neuron system has any impact on functional recovery of ischemic hemiparetic patients.Patients and Methods:This single-blind clinical trial was conducted on 24 patients with cerebrovascular accident (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…(Mean ± standard deviation, 66.6±8.92%). According to the adopted categories of 19 assessed papers, three studies were of high quality (scored 77.77% to 81.48%) (Bang et al, 2013; Motaqhey et al, 2015; Bellelli et al, 2010), 11 were of moderate quality (scored 62.96% to 74.07%) (Jaywant et al, 2016; Agosta and Sarasso, 2016; Park et al, 2014a, 2014b, 2017; Kim and Lee, 2015; Villafane et al, 2016, 2017; Pelosin et al, 2010; Song and Lee, 2016; Kim et al, 2014), and five were of low quality with scores ranging from 51.85 to 59.25% (Kim and Kim, 2012; Lee et al, 2017; Park and Kang, 2013; Santamato et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(Mean ± standard deviation, 66.6±8.92%). According to the adopted categories of 19 assessed papers, three studies were of high quality (scored 77.77% to 81.48%) (Bang et al, 2013; Motaqhey et al, 2015; Bellelli et al, 2010), 11 were of moderate quality (scored 62.96% to 74.07%) (Jaywant et al, 2016; Agosta and Sarasso, 2016; Park et al, 2014a, 2014b, 2017; Kim and Lee, 2015; Villafane et al, 2016, 2017; Pelosin et al, 2010; Song and Lee, 2016; Kim et al, 2014), and five were of low quality with scores ranging from 51.85 to 59.25% (Kim and Kim, 2012; Lee et al, 2017; Park and Kang, 2013; Santamato et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Only one study reported all items clearly (Bang et al, 2013). In addition, just five studies blinded their subjects to the intervention performed (Kim and Lee, 2015; Jaywant et al, 2016; Motaqhey et al, 2015; Park et al, 2014a; Bang et al, 2013). In seven studies, the main outcomes were measured by blinded examiners (Bang et al, 2013; Park et al, 2017; Bellelli et al, 2010; Villafane et al, 2016, 2017; Pelosin et al, 2010; Agosta and Sarasso, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations